A TRANSMISSION PROBLEM WITH NONLINEAR DAMPING AND SOURCE TERMS - Cabanillas Lapa, Eugenio (2006)
In this article we study the wave propagation over materials consisting of two components: one component is simple elastic while the other has  a nonlinear internal dampingwith elastic coefficients dependent on time; both components having source terms. Byusing the potential well method we obtain the global existence, we also show that theenergy of the system decays uniformly to zero,